Finding consensus for hamstring surgery in ambulatory children with cerebral palsy using the Delphi method. (February 2022) - Kay, Robert M; McCarthy, James; Narayanan, Unni; Rhodes, Jason; Rutz, Erich; Shilt, Jeffrey; Shore, Benjamin J; Veerkamp, Matthew; Shrader, M Wade; Theologis, Tim; Van Campenhout, Anja; Pierz, Kristan; et al.
Purpose: There is marked variation in indications and techniques for hamstring surgery in children with cerebral palsy. There is particular uncertainty regarding the indications for hamstring transfer compared to traditional hamstring lengthening. The purpose of this study was for an international panel of experts to use the Delphi method to establish consensus indications for hamstring surgery in ambulatory children with cerebral palsy. Methods: The panel used a five-level Likert-type scale to record agreement or disagreement with statements regarding hamstring surgery, including surgical indications and techniques, post-operative care, and outcome measures. Consensus was defined as at least 80% of responses being in the highest or lowest two of the five Likert-type ratings. General agreement was defined as 60%–79% falling into the highest or lowest two ratings. There was no agreement if neither of these thresholds was reached. Results: The panel reached consensus or general agreement for 38 (84%) of 45 statements regarding hamstring surgery. The panel noted the importance of assessing pelvic tilt during gait when considering hamstring surgery, and also that lateral hamstring lengthening is rarely needed, particularly at the index surgery. They noted that repeat hamstring lengthening often has poor outcomes. The panel was divided regarding hamstring transfer surgery, with only half performing such surgery. Conclusion: The results of this study can help pediatric orthopedic surgeons optimize decision-making in their choice and practice of hamstring surgery for ambulatory children with cerebral palsy. This has the potential to reduce practice variation and significantly improve outcomes for ambulatory children with cerebral palsy. Level of evidence: level V.